An Analysis of Syntax Error in Text Asking Permission and Giving Instruction Class VIII. - Muthiah, Zauzah (Lingua, 2021)
The purpose of this study was to describe the syntactic errors in the text asking permission and instruction of class VIII students of SMPN 177 Jakarta as well as the possibility of student errors. This type of research is descriptive-qualitative with data collection techniques using the results of students' answers to quizzes and observations during learning. The results showed that the errors found by the students were: (1) several students had relatively the same error opportunities in distinguishing the texts asking permission and giving instruction. Then in speaking the conversation in the placement of words that are not in accordance with the text asking permission and instruction; (2) the most dominant syntactic error is the student's error in writing the text sentence asking permission and giving instruction, meaning that the sentence which should be the text asking permission is misinterpreted in the instruction text, of course, there is an error in the message conveyed by the reader.